Students' Responses to the Application of YouTube-Based Learning Media in Class XI Fiqh Learning at MA DDI Tellu Limpoe, Sidenreng Rappang Regency - Muh. Musakkir; Sitti Jamilah Amin; Usman; Firman; Marhani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The aim of this research was: (1) to determine the implementation process of YouTube-based fiqh learning in Grade XI at MA DDI TelluLimpoe, Sidenreng Rappang Regency, and (2) to assess the student response to the implementation of YouTube-based learning media in Grade XI fiqh lessons at MA DDI TelluLimpoe, SidenrengRappang Regency. The research employed a qualitative (field research) approach with an interpretative perspective. The research instruments used were observation, interviews, and documentation. The data analysis techniques included data reduction, data presentation, and drawing conclusions. The results of this research indicated that: (1) The implementation process of YouTube-based fiqh learning in Grade XI at MA DDI TelluLimpoe, SidenrengRappang Regency, was conducted in three stages: planning, implementation, and evaluation. (2) Students responded to the implementation of YouTube-based learning media in Grade XI fiqh lessons at MA DDI TelluLimpoe, SidenrengRappang Regency. The students exhibited both positive and negative responses, which could be used as an indicator of their comfort level during the teaching and learning process. According to the students, the implementation of fiqh learning based on the YouTube application improved their learning outcomes and received positive responses. The use of visuals and audio in YouTube-based learning, along with its engaging nature, prevented boredom and facilitated better understanding of the subject matter. This indicates the effectiveness and efficiency of using the YouTube application for learning purposes.